Profil Penyesuaian Sosial Remaja yang Mengalami Kecanduan Mengakses Facebook - Pia Amanda Nurhusni (Universitas Mathla'ul Anwar Banten, 2017)
Social Adjustment Profiles Adolescence Who Have Access addicted to Facebook. The process of social adjustment of students who disrupted it can cause problems in the fulfillment of their needs. The research objective of this thesis to obtain social adjustment eighth grade students of SMP Negeri 15 Bandung who had access facebook addiction. The study used descriptive research methods. Questionnaire used was a questionnaire addiction accessing facebook and social adjustment. The results: (1) Addiction adolescence including access facebook high category and (2) the social adjustment of adolescence who access facebook categorized as low, medium and high, (3) the design of personal-social counseling services focus on reducing access facebook addiction indicators and development indicators of social adjustment.